Echocardiography and ultrasound dopplerography assessment of central and peripheral hemodynamics in children with septic shock - V.V. Yevtushenko; S.O. Kramarev; O.O. Voronov; O.M. Yevtushenko (Zaslavsky O.Yu., 2017)
Background. The severe course of sepsis is usually associated with the development of septic shock and multiple organ failure. For effective treatment, it is recommended to perform instrumental monitoring of preload, contractile capacity of the heart and tissue perfusion. We aimed to evaluate changes in central and peripheral hemodynamics by echocardiography and Doppler ultrasound in children with septic shock. Materials and methods. A retrospective study of cases of septic shock in children aged 0 to 18 years who underwent treatment in the intensive care unit was conducted. Patients were monitored for central and peripheral hemodynamics by echocardiography and Doppler ultrasound. The initial study of hemodynamic parameters was carried out over the first 3 hours after hospitalization. The second study was carried out in 24-36 hours after the hospitalization. The third study was conducted in the period of convalescence within 24-48 hours after the withdrawal of sympathomimetic drugs. Results. Thirty-four cases of sepsis associated with septic shock were investigated. In 24 (70.6 %) patients, the etiological factor was meningococcus, in 1 (2.9 %) staphylococcus, and in 9 (26.5 %) no aetiology was established. In 6 children from the study group fatal outcome occurred. Values of mean blood pressure, ejection fraction, peripheral resistance were relatively lower in the acute shock period, and increased after stabilization of hemodynamics. Evaluation of peripheral blood circulation at admission showed decreased diastolic velocity in abdominal aorta and upper mesenteric artery and systolic velocity in posterior tibial artery. The results of initial investigation demonstrated that 44.1 % patients had increased cardiac output along with decreased systemic vascular resistance ('warm shock'), and just 8.8 % had features of 'cold shock' (decreased cardiac output and increased vascular resistance). The fatal course of the disease was associated with higher heart rate, lower systolic velocity (V max) values in the truncus coeliacus and femoral artery, diastolic velocity (V min), and peripheral resistance index in the renal artery at the initial examination. Conclusions. Comprehensive study of central and regional hemodynamics parameters in children through echocardiography and Doppler ultrasound allows non-invasive diagnostic of early violations associated with septic shock and control of the effectiveness of therapeutic measures.